Aggregation ability of the main blood cells in arterial hypertension and dyslipidemia patients on rosuvastatin and non-drug treatments - I. N. Medvedev; I. A. Skoryatina; S. Yu. Zavalishina (Кардиоваскулярная терапия и профилактика)
In Russia, there is still high prevalence of arterial hypertension (AH)comorbid with dyslipidaemia (DL), which increase aggregation properties of the blood cells. It seems rational to implement statins for rapid correction of aggregation properties of blood cells in AH with DL patients.Aim. To reveal the possibilities for complex influence of rosuvastatin and non-drug treatment on aggregation properties of blood cells in AH with DL patients.Material and methods. Totally, 61 patient with AH 1-2 grade studied, with risk 3 and DL IIb type, middle age. Controls were 26 clinically healthy volunteers of the same age. All patients were prescribed rosuvastatin and non-medication treatment. Antihypertension therapy — enalapril 10 mg b. i.d. Clinical and laboratory parameters registration was performed at baseline, in 6, 12, 52, 104 weeks after treatment start. For statistics, we used t- criteria by Student.Results. At the background of therapy, there signs of DL vanished, with more rapid increase of antioxidant plasma activity and with faster normalization of lipid peroxidation level. Rosuvastatin with non-drug treatment normalized aggregation properties of red blood cells, platelets, neutrophils in as low as 6 weeks of treatment by achievement of the optimum of their aggregation realization. The treatment established the effect for whole follow-up.Conclusion. To minimize the risk of hyperaggregation of blood cells and to relieve the lipid disbalance in plasma of AH with DL patients, it is recommended for them to take rosuvastatin for long time and with strict following the recommendations on non-drug interventions.